(untitled) (International Journal of Physiotherapy, 2020)
Background: Rehabilitation following an anterior cruciate ligament reconstruction (ACLR) will allow the patient to regain his functional capacities and support him in the resumption of sports activity. Rehabilitation also aims to minimize the recurrence risk, ensuring the good development of the patient’s muscular capacities until returning to sport. Isokinetism allows the strengthening and evaluation of this muscular strength of the thigh muscle groups. Still, controversy exists about its use by resistance to knee extension in the open kinetic chain, which would cause the graft’s distension. This study aims to determine the influence of muscle strengthening of the quadriceps in the open kinetic chain by using isokinetism on the possible laxity of the anterior cruciate ligament and being able to develop risk factors for it. Methods: The study is based on a population having benefited from an ACLR with a hamstring graft six months postoperatively. Two groups are differentiated; one group exposed to isokinetic during their rehabilitation, the other group, undergoing rehabilitation without the use of isokinetism is the unexposed group. An anterior knee laxity test is performed six months postoperatively using the unexposed group. According to the same protocol, the anterior knee laxity test is performed 6 months post-operatively using all subjects’ GNRB® machine. The test results underwent statistical analysis to determine the relative risk of plastic surgery for each study group. Results: Comparing each group’s results by a univariate analysis did not reveal any significant results. Multivariate analysis to show interactions between the study groups. It was found that the use of isokinetism would seem not to affect the risk of developing distension for the majority of subjects in the exposed group. A tendency towards protection was found for exposed subjects aged between 25 and 35 regarding the graft’s distension. Also, a tendency to protection was found in the exposed subjects regarding an alteration of the graft leading to an anatomically comparable difference. Conclusion: The use of isokinetism does not seem to cause distension of the graft in patients operated on ACLR when this method is introduced three months postoperatively.